Mid‐term effects on ecosystem services of quarry restoration with Technosols under Mediterranean conditions: 10‐year impacts on soil organic carbon and vegetation development. Issue 4 (26th November 2019) - Carabassa, Vicenç; Domene, Xavier; Díaz, Elisa; Alcañiz, Josep M.
Abstract : The use of Technosols for the restoration of limestone quarries overcomes the usual "in situ" scarcity of soil and/or its poor quality. The use of mine spoils, improved with mineral and/or organic amendments, could be an efficient and environmentally friendly option. Properly treated sewage sludge from urban wastewater treatment plants could be a suitable organic amendment and fertilizer (rich in N and P) whenever its pollutant burden is low (heavy metals and/or organic pollutants). Its appropriate use could improve essential soil physical and chemical properties and, therefore, promote key ecosystem services of restored areas, such as biomass production and carbon sequestration, as well as biodiversity and landscape recovery. However, the mid‐term impacts of these restoration practices on soil functioning and their services have rarely been reported in the available literature. In this study we assess the mid‐term effects (10 years) of the use of sewage sludge as a Technosol amendment on soil organic carbon (SOC), nutrient status, and plant development in several restored quarries. Soils restored using sewage sludge showed a threefold increase in SOC compared to the corresponding unamended ones, despite the moderate sludge dosage applied (below 50 tonnes/ha). Plant cover was also higher in amended soils, and recruitment was not affected by sludge amendment at these doses. This study demonstrates that, used at an appropriate rate, sewage sludge is a good alternative for the valorization of mine spoils in quarry restoration, improving some important regulatory ecosystem services such as carbon sequestration, without compromising woody plant encroachment.